2021
DOI: 10.5604/01.3001.0015.7694
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features of pilonidal cysts of the sacrococcygeal region

Abstract: Introduction: Despite the fact that the pilonidal cyst of the sacrococcygeal region is a long-known disease, the mechanism of accumulation or absence of hair in the cyst remains unclear, which affects the accuracy of the name of the disease, as well as understanding of its pathogenesis. Aim: Aim to perform morphological examination of pilonidal cysts of the sacrococcygeal region, to determine the nature of the cysts, the frequency of hair in the cyst cavity and to determine the causes and mechanism of its accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Its internal hair is thought to be caused by the invagination of the epithelial hair follicle, leading to the generation of chronic sinus because of infection and other factors. 10 Based on the aetiology of SPS explained by the theories above, it has also been concluded that SPS has an acquired aetiology. 11 The acquired theory suggests that the main cause of pilonidal sinus disease is the swing and friction of the gluteal sulcus during movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its internal hair is thought to be caused by the invagination of the epithelial hair follicle, leading to the generation of chronic sinus because of infection and other factors. 10 Based on the aetiology of SPS explained by the theories above, it has also been concluded that SPS has an acquired aetiology. 11 The acquired theory suggests that the main cause of pilonidal sinus disease is the swing and friction of the gluteal sulcus during movement.…”
Section: Discussionmentioning
confidence: 99%
“…According to the congenital theory, congenital remnants of the epithelium or congenital depressions of the epidermis are the root causes of the disease. Its internal hair is thought to be caused by the invagination of the epithelial hair follicle, leading to the generation of chronic sinus because of infection and other factors 10 . Based on the aetiology of SPS explained by the theories above, it has also been concluded that SPS has an acquired aetiology 11 .…”
Section: Discussionmentioning
confidence: 99%